2017
DOI: 10.1001/jamapediatrics.2016.3750
|View full text |Cite
|
Sign up to set email alerts
|

Rural and Urban Differences in Neonatal Abstinence Syndrome and Maternal Opioid Use, 2004 to 2013

Abstract: Incidence rates for neonatal abstinence syndrome (NAS) and maternal opioid use increased nearly 5-fold in the United States between 2000 and 2012. 1 Previous studies suggest the incidence of NAS may be increasing rapidly in some rural states, 2 in parallel with rising rural rates of other opioid use-related conditions including hepatitis C and overdose deaths. 3,4 To our knowledge, no study has examined national trends in NAS and maternal opioid use among rural patients compared with their urban counterparts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
139
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 130 publications
(148 citation statements)
references
References 5 publications
7
139
1
1
Order By: Relevance
“…These findings are consistent with recent reports of rising neonatal abstinence syndrome incidence, 7 including disproportionate increases among neonates residing in the rural United States. 16 While substance use screening is recommended for all women during prenatal care, 17 effective provision of this service has been complicated by a recent surge in legislation penalizing pregnant women for disclosing substance use. Punitive legislation has disproportionately impacted women in rural states, 18 where additional barriers to treatment may already exist, including a scarcity of addiction providers willing to treat pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with recent reports of rising neonatal abstinence syndrome incidence, 7 including disproportionate increases among neonates residing in the rural United States. 16 While substance use screening is recommended for all women during prenatal care, 17 effective provision of this service has been complicated by a recent surge in legislation penalizing pregnant women for disclosing substance use. Punitive legislation has disproportionately impacted women in rural states, 18 where additional barriers to treatment may already exist, including a scarcity of addiction providers willing to treat pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal OUD and NAS disproportionately affect rural communities, where poverty levels are higher and where health care access is more limited . From 2004‐2013, the incidence of both NAS and maternal OUD increased more rapidly in rural counties, where rates rose from 1.2 to 7.5 per 1,000 compared to urban counties, where rates rose from 1.4 to 4.5 per 1,000 .…”
mentioning
confidence: 99%
“…Maternal OUD and NAS disproportionately affect rural communities, where poverty levels are higher and where health care access is more limited . From 2004‐2013, the incidence of both NAS and maternal OUD increased more rapidly in rural counties, where rates rose from 1.2 to 7.5 per 1,000 compared to urban counties, where rates rose from 1.4 to 4.5 per 1,000 . Further, compared with their urban peers, rural women and infants with opioid‐related diagnoses are more likely to be from lower‐income families, and rural infants are more likely to be transferred to another hospital following delivery .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The recent rise of opioid use in pregnancy and NAS has disproportionately occurred in rural areas (9, 10)** Using administrative data from 2004 to 2013, Villapiano et al(11)* found the incidence of NAS per 1000 hospital births increased from 1.2 to 7.5 among rural infants and from 1.4 to 4.8 among urban infants. The demographic differences between rural and urban areas is also apparent in state surveillance data.…”
Section: Changing Epidemiologymentioning
confidence: 99%